REMUNERATION JUSTICE IN ISLAMIC HIGHER EDUCATION: A STAKEHOLDER PERSPECTIVE - Azharsyah Ibrahim; Abdul Jalil Salam; Syahminan Syahminan; Ana Fitria (Univeristas Islam Bandung, 2020)
This study generally intends to analyze perception of remuneration justice from the perspectives of stakeholders in Indonesian Public Islamic Universities (PTKIN) that have acquired BLU status. Specifically, this study aims to measure the level of distributive and procedural justice on the implementation of remuneration at selected PTKIN. The respondents of this study are the beneficiaries and remuneration policy makers from 11 PTKIN that have implemented and paid the remuneration at the time of the study. Additional data are obtained from interviews with nine policy makers from the selected PTKIN. The data are analyzed using descriptive percentages method. The results show that in general the implementation of remuneration at the selected PTKIN in included within “fair” category as perceived by the stakeholders. Partially, respondents perceive procedural justice as